The functional response and resilience in small waterbodies along land‐use and environmental gradients. (24th April 2018) - Thornhill, Ian A.; Biggs, Jeremy; Hill, Matthew J.; Briers, Robert; Gledhill, David; Wood, Paul J.; Gee, John H. R.; Ledger, Mark; Hassall, Christopher
Abstract: There is growing recognition of the essential services provided to humanity by functionally intact ecosystems. Freshwater ecosystems are found throughout agricultural and urban landscapes and provide a wide range of ecosystem services, but globally they are also amongst the most vulnerable. In particular, ponds (lentic waters typically less than 2 ha), provide natural flood management, sequester carbon and hold significant cultural value. However, to inform their management it is important to understand (1) how functional diversity varies in response to disturbance and (2) the link between biodiversity conservation and ecosystem function. In this study, a meta‐analysis of seven separate pond studies from across England and Wales was carried out to explore the effect of urban and agricultural land‐use gradients, shading, emergent vegetation, surface area and pH upon groups of functionally similar members of the macroinvertebrate fauna. Functional effect groups were first identified by carrying out a hierarchical cluster analysis using body size, voltinism and feeding habits (18 categories) that are closely related to biogeochemical processes (e.g. nutrient and carbon recycling). Secondly, the influence of the gradients upon effect group membership (functional redundancy—FR) and the breadth of traits available to aid ecosystem recovery (response diversity) was assessed using species counts and functional dispersion (FDis) using 12 response traits. The effect of land‐use gradients was unpredictable, whilst there was a negative response in both FR and FDis to shading and positive responses to increases in emergent vegetation cover and surface area. An inconsistent association between FDis and FR suggested that arguments for taxonomic biodiversity conservation to augment ecosystem functioning are too simplistic. Thus, a deeper understanding of the response of functional diversity to disturbance could have greater impact with decision‐makers who may relate better to the loss of ecosystem function in response to environmental degradation than species loss alone. Abstract : Whilst land‐use change has been well documented to negatively impact freshwater habitats and their biodiversity, the functional response of these communities is little researched. We asked, how does the number of species sharing similar functional traits (redundancy), and their respective response trait diversity change along land‐use and local environment gradients? An inconsistent effect of land‐use upon functional diversity was found suggesting context‐dependency. Local environmental variables were more consistent and significant in their influence. A partial disconnect was observed between functional redundancy and response diversity, with implications for biological conservation.